Development and Validation of a Specific Self-Efficacy Scale in Adherence to a Gluten-Free Diet - Fueyo-Díaz, Ricardo; Magallón-Botaya, Rosa; Gascón-Santos, Santiago; Asensio-Martínez, Ángela; Palacios-Navarro, Guillermo; Sebastián-Domingo, Juan J. (Frontiers in Psychology, 2018)
The aim of this study is to develop a scale to assess the levels of specific self-efficacy in order to enhance adherence to a gluten-free diet and the life quality of celiac patients. Celiac disease is a chronic small intestinal immune-mediated enteropathy precipitated by exposure to dietary gluten in genetically predisposed people. The only treatment is a strict lifelong gluten-free diet. Within the framework of Social Cognitive Theory, expectation of self-efficacy is understood as the degree in which a person believes himself to be capable of performing a certain task (e. g. adhering to a gluten free diet), a construct which has been widely studied in its relation with adopting healthy behaviors, but scarcely in relation to celiac disease. A validation study was carried out in various stages: preparation of the protocol; construction of the questionnaire and a pilot run with 20 patients; validation of the scale with 563 patients and statistical analysis. A 25-item scale was developed. Feasibility was excellent. Factorial analysis pointed to the existence of 5 factors that explained 70.98% of the variance with a Cronbach alpha of 0.81 for the scale overall and between 0.64 and 0.91 for each factor. The scale showed a Spearman’s Rho coefficient of 0.279 with the General self-efficacy Scale. This easily applicable scale provides good psychometric properties for evaluating specific self-efficacy of celiac patients in adhering to treatment. It seeks to be the first scale that provides not only a measurement of specific self-efficacy in celiac disease, but also to determine its levels for each of the areas as a first step towards designing interventions of self-management and empowerment programs to cope with the disease.